2013
DOI: 10.1111/j.1610-0387.2012.08071.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug supply for psoriasis – results from a national pharmacy network

Abstract: Background: In Germany, drugs are to a large extent provided by pharmacies. Thus, investigations in pharmacies permit drug usage studies both on patients receiving prescribable drugs and using self-medication. The current study evaluated the quality of medical care, disease burden and spectrum of treatments for patients with psoriasis in a nationwide network of pharmacies. Patients and methods: A nationwide cross-sectional study was conducted in 61 pharmacies. Patients with psoriasis vulgaris who came to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
6
0
4
Order By: Relevance
“…The socio‐demographic and clinical features of the PsoBest patients show some differences from the patients in the national studies PsoHealth in 2007 and PsoPharm in 2010 (Table ). The patients in PsoBest had a shorter duration of disease (18.2 vs. 21.3 years) and were younger (47.3 vs. 51.5 years) than those in PsoHealth and PsoPharm.…”
Section: Resultsmentioning
confidence: 91%
“…The socio‐demographic and clinical features of the PsoBest patients show some differences from the patients in the national studies PsoHealth in 2007 and PsoPharm in 2010 (Table ). The patients in PsoBest had a shorter duration of disease (18.2 vs. 21.3 years) and were younger (47.3 vs. 51.5 years) than those in PsoHealth and PsoPharm.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, studies on psoriasis care and self-medication in Germany by pharmacies have shown that very few patients buying medication and doing self-medication in Germany do not refer to a prescription. Furthermore most Germans are insured, since health care provision is based on a statutory health insurance system [34]. Until now, only few validation studies for routine data of German statutory health insurances exist, and the true underlying number of children with each ICD-10 diagnosis can only be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Die soziodemografischen und klinischen Merkmale der PsoBest-Patienten weichen deskriptiv gegenüber den Patientenmerkmalen ab, die in der nationalen Versorgungsstudie PsoHealth im Jahr 2007 [25] und PsoPharm 2010 [26] gefunden wurden (Tabelle 2). Die Patienten in PsoBest hatten im Vergleich zu den Patienten in PsoHealth und PsoPharm eine kürzere Erkrankungsdauer (18,2 vs. 21,3 J.)…”
Section: Soziodemografische Und Klinische Merkmaleunclassified
“…Bezüglich der letzten Vortherapie unterscheiden sich die in PsoBest eingeschlossenen Patienten durch einen deutlich höheren Anteil an Systemtherapeutika und einem geringeren Anteil an topischen Medikamenten von Patienten mit Psoriasis anderer Versorgungsstudien (Abbildung 6) [25][26][27][28][29].…”
Section: Soziodemografische Und Klinische Merkmaleunclassified
See 1 more Smart Citation